Cardiac ischaemic stress in the haemodialysis patient - Crowley, Lisa E. (2016)
Haemodialysis patients experience elevated levels of cardiovascular morbidity and mortality that has a profound effect on not only their survival and quality of life but also increases the already high social and economic cost of dialysis. It is increasingly appreciated that the circulatory stress caused by dialysis is a significant contributing factor and helps to accelerate the end organ damage this group of patients is known to experience. In particular the cumulative ischaemic insult suffered by the heart during haemodialysis sessions has been suggested as one of the principal drivers of heart failure and sudden cardiac death – the two principal causes of death in this population.